Isolasi dan Karakterisasi Nano Hemiselulosa dari Tandan Kosong Kelapa Sawit (Elaeis guineensis Jacq.) - Ritonga , Septi Ani; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari; Yuniarti, Rafita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Empty Fruit Bunches (EFB) of oil palm (Elaeis guineensis Jacq.) are a significant agricultural waste from the palm oil industry, currently underutilized. EFB contains lignocellulosic components, including hemicellulose (22.84%), which has potential applications in the pharmaceutical sector as a hydrophilic polymer. Objective: This study aimed to isolate and characterize hemicellulose and nano-hemicellulose from oil palm EFB using an environmentally friendly green chemistry method with low-concentration reagents. Methods: This experimental research began with the purposive sampling of EFB. Hemicellulose was isolated using a sequential process with 0.1 N NaOH, 0.1 N HCl, and 70% ethanol. The resulting hemicellulose was then nano-sized using a ball mill technique. Characterization included organoleptic tests, solubility tests, Fourier Transform Infrared (FTIR) spectroscopy, Particle Size Analyzer (PSA), and Scanning Electron Microscope (SEM). Results: The isolation process from 500 g of EFB powder yielded 16.7 g of hemicellulose, with a yield of 3.34%. FTIR analysis identified key functional groups (O-H, C-H, C=O, C-O, C=C) in both hemicellulose and nano-hemicellulose, confirming their chemical similarity. SEM analysis at 500x magnification revealed a more regular particle structure with distinct cavities, indicating a swelling effect from the alkali treatment. PSA confirmed the nano-scale size of the processed particles. Conclusion: Hemicellulose and nano-hemicellulose were successfully isolated from oil palm EFB using a simple green chemistry method. The characterized nano-hemicellulose showed properties suitable for potential development as a carrier in pharmaceutical formulations.